Sensory quality and fatty acids composition of male local duck meat with Santoquin, vitamin E and C suplementation in ration - Maijon Purba; E.B Laconi; P.P Ketaren; C.H Wijaya; P.S Hardjosworo (Indonesian Center for Animal Research and Development (ICARD), 2010)
Fishy odor is one of off odor attributes local duck meat. Off odor reduces consumer preference on duck meat. This experiment was conducted to evaluate effect of fish meal levels and antioxidant in diets on the off odor intensity and fatty acid composition of local duck meat. The experiment was designed based on 2x3factorial experiment. The first factor was two fish meal level: low (TIR) and high (TIT), and second factor was three antioxidant level: none, 150 ppm santoquin (Sq) + 400 IU vitamin E (VE), and 400 IU vitamin E (VE) + 250 mg vitamin C (VC)/kg diet. One hundred and twenty MA (Mojosari♂ x Alabio♀) day old male duck were allocated into six treatments: (1) TIR, (2) TIR + 150 ppm Sq + 400 IU VE, (3) TIR + 400 IU VE + 250 mg VC (4) TIT, (5) TIT + 150 ppm Sq + 400 IU VE, and (6) TIT + 400 IU VE + 250 mg VC. Off odor intensity on raw and boiled meat, and fatty acid composition in boiled duck meat were used as parameters. The result indicated that fish meal levels did not significantly (P>0.05) affect the off odor intensity in raw and boiled meat. However, antioxidants supplementation significantly (P<0.05) reduced off odor intensity in both raw and boiled meat. Antioxidants supplementation in diet prevented the unsaturated fatty acids from lipid oxidation in boiled meat. This experiment suggests that supplementation of 150 ppm santoquin + 400 IU vitamin E or 400 IU vitamin E + 250 mg vitamin C to the duck diets were effective in reducing off odor and hence increased the sensory quality of duck meat. Key words: Local Duck, Antioxidants, Fish Meal, Fatty Acids, Quality Sensory